An Analysis of Students’ Reading Comprehension at an Islamic Institute in Jambi - Indrayadi, Toni (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
This study examines each reading comprehension indicator and reading comprehension in general. Forty-five first-semester students of the English Education Department at Public Islamic Institute Jambi, Indonesia, which comprised of twenty-one males and twenty-four females voluntarily participated in this study. They were purposively selected as the sample of the research. This study used six indicators of reading comprehension and reading comprehension in general data. The descriptive quantitative approach was employed in this study as the research methodology. The descriptive statistic of SPSS 23 was applied to analyze the mean and standard deviation of six reading comprehension and reading comprehension in general. The criteria referenced interpretation and norm-referenced interpretation investigated interval of six reading comprehension and reading comprehension in general. The result of descriptive statistics and criteria referenced interpretation, and norm-referenced interpretation analysis showed five reading comprehension indicators in terms of author purpose, topic details, reference, and vocabulary in context in moderate criteria, except the main idea in which in high criteria. The reading comprehension was in moderate criteria similar to five reading comprehension indicators. Therefore, English lecturers hope to select an appropriate strategy and be well prepared to teach reading.